2014
DOI: 10.1037/a0034667
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of family focused therapy with populations at clinical high risk for psychosis: Effects on interactional behavior.

Abstract: Objective This study investigated whether family focused therapy (FFT-CHR), an 18-session intervention that consisted of psychoeducation and training in communication and problem solving, brought about greater improvements in family communication than enhanced care (EC), a 3-session psychoeducational intervention, among individuals at clinical high risk for developing psychosis. Method This study was conducted within a randomized controlled trial across 8 sites. We examined 10-min problem-solving discussions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 69 publications
4
56
2
Order By: Relevance
“…40,[49][50][51][52][53][54][57][58][59][60][61][62][63] Our findings support our clinical experiences and have provided greater depth to our understanding of this complex problem. Clinically, we observed that post-TBI irritability is often not discussed unless brought up by the provider.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…40,[49][50][51][52][53][54][57][58][59][60][61][62][63] Our findings support our clinical experiences and have provided greater depth to our understanding of this complex problem. Clinically, we observed that post-TBI irritability is often not discussed unless brought up by the provider.…”
Section: Discussionsupporting
confidence: 89%
“…40,54 We found that irritability is often experienced in interactions with one's spouse or significant other. In fact, interpersonal communication difficulties experienced by people with a history of TBI often exacerbate the irritability.…”
Section: Relational Dimensionmentioning
confidence: 96%
“…Further, our findings align with prior evidence that caregivers of youth with schizophrenia spectrum disorders in particular experience high levels of stress and psychological burden (Knock et al, 2011) that may negatively impact familial relationships that play an important role in treatment engagement and outcomes. Creating or maintaining positive parent-child relations can be an important prognostic factor for young people at risk for psychosis (O'Brien et al, 2008(O'Brien et al, , 2014, highlighting another potential target for CHR intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in communication was reported elsewhere,4 but the effects of a prevention plan and acquiring coping and problem-solving skills were not evaluated.…”
Section: Limitationsmentioning
confidence: 99%